The social economic situation and its impact on labour migration in the Slovak Republic - Mačkinová, Monika (Acta Salus Vitae, 2017)
The economic crisis has affected most of the countries in the world and its consequences felt by nearly everyone in various fields and forms of life. Among its most serious consequences is included the rising of unemployment, as well as the expansion of poverty, which did not avoid the Slovak Republic, too. The current economic crisis, as well as the previous one from 1929, are related to the indebtedness of citizens when by consequences of changes at the labour markets may occur problems with repaying of their debts. Resulting in commitments to several of institutions which are citizens not able to pay, unemployment, as well as the deterioration of the living standards of the affected family.